1983
DOI: 10.1016/0039-6028(83)90231-5
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic ellipsometric investigation of the clean and oxygen exposed Ni(110) surface

Abstract: Dynamical ellipsometric investigationsof the initial oxidation of the Ni(ll0) surface have been performed.Ellipsometry appears to be well suited to distinguish between chemisorbed oxygen and nickel oxide on the surface. Annealing at 740 K causes the nucleation of nickel oxide to proceed faster than at 570 K. After equal exposures however, the nucleation is slower with an oxygen pressure of 2X10W7 Torr than with a pressure of 1.3X IO-' Torr. Spectroscopic elhpsometric measurements (400-800 nm) have been perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
3
3
0
Order By: Relevance
“…the ellipsometric parameters A and 4 showed a small decrease. This was of the same order of magnitude (6A = 0.2") 81) = 0.02" ), and had a similar relaxation time (t = 45 min) as reported for Ni(ll0) [23]. This decrease in A and J/ is caused by the segregation of oxygen towards the surface.…”
Section: Influence Of Cold Worksupporting
confidence: 77%
See 3 more Smart Citations
“…the ellipsometric parameters A and 4 showed a small decrease. This was of the same order of magnitude (6A = 0.2") 81) = 0.02" ), and had a similar relaxation time (t = 45 min) as reported for Ni(ll0) [23]. This decrease in A and J/ is caused by the segregation of oxygen towards the surface.…”
Section: Influence Of Cold Worksupporting
confidence: 77%
“…A 3 ML coverage has also been reported for Ni(ll0) [23] and Ni(lOO) [6,7]. Mitchel et al [8] reported that the oxidation is strongly influenced by the amount of carbon present at the surface prior to oxidation.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…TDP's were also observed with nickel [8] at the same energy values as reported by Becker and Hagstrum [9]. At 740 K the TDP's were totally absent, except for a small shoulder around 200 eV.…”
Section: Methodssupporting
confidence: 70%